1993
DOI: 10.1111/j.1464-5491.1993.tb00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Clinical Characteristics of South Asians and Europeans in Coventry

Abstract: A house to house survey in Foleshill, Coventry, compared risk factors for Type 2 diabetes and ischaemic heart disease (IHD) among adult United Kingdom Europeans (n = 5508, 64% screened) and South Asians (n = 4395, 84% screened). Those with a high glucose and a randomized 10% of others had a glucose tolerance test while those with previously diagnosed diabetes (104 Europeans, 223 South Asians) were re-interviewed in more detail. By the age of 29 years, South Asians had higher 2 h glucose 5.4 +/- 1.0 vs 4.84 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 29 publications
(1 reference statement)
3
26
1
Order By: Relevance
“…In the present study, the younger age of onset of Type 2 diabetes in chewers compared with non-chewers is consistent with the fact that a study conducted in Coventry (UK) revealed that South Asian subjects developed Type 2 diabetes at an earlier age than the European subjects [19]. Furthermore, these individuals required supplemental hypoglycaemic medication more frequently and at a younger age than the Europeans [19].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In the present study, the younger age of onset of Type 2 diabetes in chewers compared with non-chewers is consistent with the fact that a study conducted in Coventry (UK) revealed that South Asian subjects developed Type 2 diabetes at an earlier age than the European subjects [19]. Furthermore, these individuals required supplemental hypoglycaemic medication more frequently and at a younger age than the Europeans [19].…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, these individuals required supplemental hypoglycaemic medication more frequently and at a younger age than the Europeans [19]. The younger age of onset observed in our study also paralleled the increased prevalence of the areca nut habit in younger people, reflecting the comparatively recent uptake of the habit over the last 40 years.…”
Section: Discussionsupporting
confidence: 68%
“…Hyperglycemia, for example, is consistently the strongest risk factor for both diabetic peripheral neuropathy (36,37) and PAD (38), yet glycemic control in Asians is, paradoxically, either similar to or worse than Europeans (31,39). Similarly, Asian lipid profiles are also worse than Europeans (2), yet dyslipidemia predicts incidence of diabetic PAD and neuropathy (38,40).…”
Section: Discussionmentioning
confidence: 99%
“…This differs from other ethnic groups, such as South Asians, who are intrinsically hyperinsulinemic, independent of any given level of obesity (34). An inherited change to adapt to this mitochondrial haplotype may have occurred, therefore, to assist with survival of babies (i.e., as a counterbalance to the "small baby" drive while maintaining any benefits of the mitochondrial haplotype later in life).…”
Section: Hyperleptinemia In Offspring Of Normal Polynesian Womenmentioning
confidence: 99%